Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.foodcont.2017.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Microwave oven safety: A food safety consumer survey in Malaysia

Abstract: Microwave oven is an indispensable tool in every household. However, the proper usage of the microwave ovens was neglected and thus, causing food safety concerns, especially microbiological hazard in microwaved heated food. Therefore, a survey was initiated to gauge the consumer's knowledge of microwave oven safety concerning the food safety of reheated food. A total of 29 survey questions was designed that covered 5 demographic questions and 24 others on the knowledge and practice of microwave oven safety and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 6 publications
0
8
0
3
Order By: Relevance
“…The overall food safety knowledge of adult consumers was considered good but was seriously lacking in knowledge of temperature control. Similarly, a survey on microwave oven safety revealed low level of microwave oven knowledge and safety practices [15]. More than 70% of the respondents did not reheat food periodically nor stir their food midway of the reheating process.…”
Section: Introductionmentioning
confidence: 99%
“…The overall food safety knowledge of adult consumers was considered good but was seriously lacking in knowledge of temperature control. Similarly, a survey on microwave oven safety revealed low level of microwave oven knowledge and safety practices [15]. More than 70% of the respondents did not reheat food periodically nor stir their food midway of the reheating process.…”
Section: Introductionmentioning
confidence: 99%
“…Os resultados das análises físico-químicas obtidos encontram-se na Tabela 1, onde são apresentados os valores médios seguido do desvio padrão das amostras. O pH médio encontrado foi de 3,57 (diet) e 3,70 (tradicional), esses valores são concordantes do que os encontrados por Souza et al (2018) para a gelatina de mel (3,32) e por Palazzo (2008) para a gelatinas de framboesa também em duas formulações, em que a diet apresentou valores na faixa de 3,77 a 3,96 e para as marcas tradicionais entre 3,72 a 4,00.…”
Section: Resultado E Discussãounclassified
“…Ocorre primeiramente ruptura das pontes de hidrogênio pela rotação dos dipolos da água livre (devido a tensão no campo e a mudança de polaridade) e migração iônica, ou seja, sais livres (há colisão entre os componentes) e, portanto, conversão da energia de micro-ondas para energia térmica com elevação da temperatura no interior do alimento. Há ação sobre as moléculas de água promovendo aquecimento (New et al, 2017;Velho, 2016;Pereira, 2007;Buffler, 1993;Decareau;Peterson, 1986).…”
unclassified
“…A consumer survey conducted by New, Thung, Premarathne et al (2017) indicated moderate levels of food safety knowledge a random group of Malaysian consumers. Surprisingly, Norazmir et al (2012) reported high levels of food safety knowledge among secondary school students in Johor.…”
Section: Consumer Awarenessmentioning
confidence: 99%